ANALISIS BIBLIOMETRIK PENGGUNAAN CHAT GPT BERBASIS DATA GOOGLE SCHOLAR: Studi Komprehensif Penggunaan Teknologi ChatGPT dalam Publikasi Ilmiah Tahun 2018-2023 - Sarmuni Sarmuni; Ahmad Tabrani (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
The goal of this study is to analyze systematic bibliographic analysis step by step with VOSViewer. As a result, the authors concluded that Google Scholar's data-driven ChatGPT may be utilized to interact with other scientists on research projects. This study shows the findings of data analysis on the use of ChatGPT and its evolution during the last six years (2018-2023) using mapping tools and the application VOSViewer. To describe the use of chatGPT, bibliometric analysis can generate network visualizations depending on the specified theme. In this study, we employed a quantitative research method combined with a bibliometrical descriptive approach. Based on the results of the journal grouping, the researchers discovered the most publications between 2018 and 2023. There are numerous opportunities to learn new things in this theme. As a result, this future study is expected to serve as a source of material for future research and the identification of research topics.